Pengaruh Reward dan Disiplin Kerja Terhadap Produktivitas Kinerja Karyawan BPN Aceh Barat (Studi Kasus Pada Kantor Pertanahan (BPN) Kabupaten Aceh Barat) - Jumbratu Rahma; Cut Devi Maulidasari (Cattleya Darmaya Fortuna, 2021)
This is a lesson aims to confirm and check the impact of incentives and work discipline in the workplace employee show productivity. This special location study finished in land office (BPN) of West Aceh Regency. This study's sample consisted of all employees land office (BPN) of West Aceh Regency, totaling 37 people, sampling Saturated Sampling was used in this study (Non Probability Sampling). The variables in this study are as follows reward (X1), work discipline (X2), as well as employee performance productivity (Y). The result of multiple linear regression analysis in this research explain that the prize and work Variable discipline has positive influence on employee performance productivity with the equation Y = 8.096 + 0.483X1 + 0.315X2 + e. Based on t and f. test outcomes is stated that reward variable as well as several work disciplines or simultaneously (simultaneously) have a significant and positive influence in terms of employee performance productivity, this can be proven by the reward variable tcount > ttable (4,651 > 2.03224), and the work discipline variable tcount > ttable (2.584 > 2.03224), and the f test results are proven by Fcount > Ftable (76,359 > 3.27) and the significance level is less than 0.05. And The coefficient of determination test results show that ability of the reward variable (X1) and exertion discipline (X2) in explaining the employee productivity variable (Y) was 80.7% and the remaining 19.3% was not explained as determined by another variable discussed in this research. As a result, the West Aceh Land Office can conclude that there is a positive interaction between reward and work discipline variables on employee performance and productivity variables (BPN). As a result, as the reward and work discipline increase, so will the productivity of employee performance.